Early inhibition of the renin‐angiotensin system improves the long‐term graft survival of single pediatric donor kidneys transplanted in adult recipients. (19th March 2013) - Zhang, Rubin; LaGuardia, Heather; Paramesh, Anil; Mills, Katherine; Killackey, Mary; McGee, Jennifer; Alper, Brent; Simon, Eric; Lee Hamm, Lotuce; Slakey, Douglas
Summary Transplanting single pediatric donor kidneys into adult recipients has an increased risk of hyperfiltration injury and graft loss. It is unknown if renin‐angiotensin system (RAS) blockers are beneficial in this setting. We retrospectively analyzed 94 adults who received single kidneys from donors <10 years old during 1996–2009. The recipients were divided into group 1 with RAS blockers (n = 40) and group 2 without RAS blockers (n = 54) in the first year of transplant. There was no significant difference in any donor/recipient demographic between the two groups. Graft function, incidence of delayed graft function, acute rejection, and persistent proteinuria were not statistically different either. Kaplan–Meier estimated death‐censored graft survivals were significantly better in group 1 than in group 2: 95 vs. 81.2%, 82.4 vs. 61.2%, 72.6 vs. 58.5%, and 68.5 vs. 47.2% at 1, 3, 5, and 7 years, respectively (log rank P = 0.043). Multivariable analysis found persistent proteinuria was a risk factor for graft loss (OR 2.70, 95% CI 1.33–5.49, P = 0.006), while RAS blockers reduced the risk of graft loss (OR 0.38, 95% CI 0.18–0.79, P = 0.009). Early RAS blockade therapy in the first year of transplant is associated with superior long‐term graft survival among adults transplanted with single pediatric donor kidneys.